Disordered eating and its association with overweight and health-related quality of life among adolescents in selected high schools of Tehran - Jalali-Farahani, Sara; Chin, Yit Siew; Mohd Taib, Mohd Nasir; Amiri, Parisa (Springer, 2015)
This study aimed to determine the association between disordered eating and overweight and also health-related quality of life (HRQOL) among adolescents in high schools of Tehran. The participants were 465 adolescents, aged 14–17 years. After anthropometric measurements, body mass index-for-age and body weight status were determined using World Health Organization cut offs. The Eating Attitudes Test-26 (EAT-26) and Pediatric Quality of Life Inventory (PedsQL™4.0) were used to assess disordered eating and HRQOL, respectively. Disordered eating was prevalent in 18.9 % of adolescents, with higher prevalence in girls (26.4 %) compared to boys (11.8 %; χ2:16.29, p < 0.05). Disordered eating was associated with overweight in girls (χ2 = 11.07, p < 0.05), but not in boys (χ2 = 2.01, p = 0.16). Disordered eating was associated with poor HRQOL especially in psychosocial domains of HRQOL. Considering the high prevalence of disordered eating and its association with overweight and poor HRQOL, preventive interventions targeting adolescents are recommended.